Analisis Yuridif Pelaksanaan Eksekusi Jaminan Bank Menggunakan Parate Eksekusi Ditinjau dari Undang-Undang Nomor 4 Tahun 1994 - Agustianto Agustianto; Jesicha Octavia (Fakultas Hukum, Universitas Internasional Batam, 2018)
Collaterals are the only factor that is used to assess in determining the size of the loan, which is often encountered in the banking world is usually a lot of debtors who pledge the land certificate as collateral for the disbursement of funds from creditors. Land certificate is an object of guaranteed from the Mortgage Right that if the debtor can be executed directly by the creditor if the debtors can’t pay the debt under Article 6 UUHT (parate execution) but its implementation is still hampered by the need to request court case. In conducting this research, researchers used a type of normative legal research where research focused on assessing the application of norms or norms in positive law about the right of dependents by using statutory approach and case approach. Data analysis which applied in this Thesis Research is by qualitative data analysis. The point is an analysis based on the data obtained, then developed into a hypothesis. Parate Execution of Dependent Rights under article 6 of the Mortgage Rights Act has an important role in resolving non-performing loans. Parate execution of mortgages acts as an alternative to an effective and efficient non-performing loan settlement compared to execution through the district court. The barriers that occur in execution of mortgage rights by using parate execution is the execution parate execution is still not optimal because there is still doubt from the creditor related procedural to the legal standing of execution under section 6 of the Mortgage Rights Act.